1994
DOI: 10.1042/bj3030709
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of ATPase activity associated with maize (Zea mays) annexins

Abstract: An ATPase activity is associated with maize (Zea mays) annexins. It has a pH optimum of 6.0, shows Michaelis-Menten kinetics and is not stimulated by Ca2+, Mg2+, EDTA or KCl; it is not inhibited by vanadate, molybdate, nitrate or azide, but N-ethylmaleimide inhibits by approximately 30% at 1-2 mM. These properties indicate that the activity is unlike other ATPases, although it has many features in common with the myosin ATPase. Gel filtration shows that the ATPase activity is mainly associated with a 68 kDa pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 35 publications
2
45
2
Order By: Relevance
“…The primary structure is very similar in the type-I1 Ca*+-binding domains of the two annexins (see above), so this may mean that other, lower-affinity sites are important in these annexins; this has proved to be the case for annexin XII (Luecke et al, 1995). An in vivo association of p33 a n d p35 is also a real possibility; we found no evidence in any of our library screens for a cDNA representing the p68 annexin present in coleoptiles (Blackbourn , et al, 1991;McClung et al, 1994) and in root tips (data not shown). The overexpression of the maize annexins is therefore an important goal made more accessible by the work described here because it should allow structure determinations and resolution of questions about Ca2+ binding and a ~3 3 1~3 5 association.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…The primary structure is very similar in the type-I1 Ca*+-binding domains of the two annexins (see above), so this may mean that other, lower-affinity sites are important in these annexins; this has proved to be the case for annexin XII (Luecke et al, 1995). An in vivo association of p33 a n d p35 is also a real possibility; we found no evidence in any of our library screens for a cDNA representing the p68 annexin present in coleoptiles (Blackbourn , et al, 1991;McClung et al, 1994) and in root tips (data not shown). The overexpression of the maize annexins is therefore an important goal made more accessible by the work described here because it should allow structure determinations and resolution of questions about Ca2+ binding and a ~3 3 1~3 5 association.…”
Section: Discussioncontrasting
confidence: 37%
“…ATPase activity in maize annexins described by McClung et al (1994) and subsequently confirmed for tomato by Calvert et al (1996). There' are no Walker-type nucleotide binding sites (Walker et al, 1982) in the predicted amino acid sequence, but not a11 nucleotide binding / hydrolyzing proteins have these (Schaap et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In plant tissues ATPase activity is associated with maize annexins (McClung et al, 1994). The highest levels of activity are found in the fractions in which a 68-kD annexin band is enriched.…”
Section: Blndlng Partners and Enzyme Activitymentioning
confidence: 86%
“…Some of the plant annexins have been shown to possess intrinsic phosphodiesterase activity (Calvert et al, 1996;McClung et al, 1994). Annexins were also suggested to play various roles in secretion and ripening processes (Blackbourn et al, 1992;Clark et al, 1992;Clark and Roux, 1995).…”
Section: Introductionmentioning
confidence: 99%